Effort to Improve Outcomes Summary Material of Number Through The Problem Based Learning Model - Suwarni, Tri (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in Mathematics in grade III elementary schools with the Problem Based Learning (PBL) learning model. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 59%. In the second cycle students who completed after carrying out the post test were 87%. These results indicate that the Problem Based Learning (PBL) learning model can improve the learning outcomes of students, especially Class III Mathematics at SDN 2 Pagergunung